Exploring Class I polyhydroxyalkanoate synthases with broad substrate specificity for polymerization of structurally diverse monomer units - Sivashankari, Ramamoorthi M; Mierzati, Maierwufu; Miyahara, Yuki; Mizuno, Shoji; Nomura, Christopher T.; Taguchi, Seiichi; Abe, Hideki; Tsuge, Takeharu (Frontiers in Bioengineering and Biotechnology, 2023)
Polyhydroxyalkanoate (PHA) synthases (PhaCs) are key enzymes in PHA polymerization. PhaCs with broad substrate specificity are attractive for synthesizing structurally diverse PHAs. In the PHA family, 3-hydroxybutyrate (3HB)-based copolymers are industrially produced using Class I PhaCs and can be used as practical biodegradable thermoplastics. However, Class I PhaCs with broad substrate specificities are scarce, prompting our search for novel PhaCs. In this study, four new PhaCs from the bacteria Ferrimonas marina, Shewanella pealeana, Plesiomonas shigelloides, and Vibrio metschnikovii were selected via a homology search against the GenBank database, using the amino acid sequence of Aeromonas caviae PHA synthase (PhaCAc), a Class I enzyme with a wide range of substrate specificities, as a template. The four PhaCs were characterized in terms of their polymerization ability and substrate specificity, using Escherichia coli as a host for PHA production. All new PhaCs were able to synthesize P(3HB) in E. coli with a high molecular weight, surpassing PhaCAc. The substrate specificity of PhaCs was evaluated by synthesizing 3HB-based copolymers with 3-hydroxyhexanoate, 3-hydroxy-4-methylvalerate, 3-hydroxy-2-methylbutyrate, and 3-hydroxypivalate monomers. Interestingly, PhaC from P. shigelloides (PhaCPs) exhibited relatively broad substrate specificity. PhaCPs were further engineered through site-directed mutagenesis, and the resulting variants resulted in enzymes with improved polymerization ability and substrate specificity.